A Critique on the Book Jurisprudence and Party Governance - Reza Mirzad; Maqsood Ranjbar; Mohammad Hossein Asadi Davoodabad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The party is one of the important components that has an important place in democratic systems. In fact, the party is the link between the practice of governance and the standards of governance. Davood Farihi in his book Jurisprudence and Party Governance tries to reconcile political jurisprudence with the government. It is related to the emergence of parliament and the concept of law in the contemporary era and explains the position of parties in the Islamic political system. The results of Farihi’s efforts show that the “party issue” in political jurisprudence is a logical extension of jurisprudence’s confrontation with the modern government. It is jurisprudential “but the fact is that the party in Iran is not jurisprudential and in this article, we criticize “the issue of the party in Iran is jurisprudential” in a descriptive and analytical way and based on library studies.